BIODEGRADABLE PLASTIC (PHB) FROM BACTERIA COLLECTED FROM GOPALPUR BEACH, BHUBANESWAR - KUMARI, DIPALI; JAIPURIAR, DIPTI SONI; KANCHANA, PARIJATHAM; VARMA, SIBYALA MALATHI; GURJA, SONY (International Journal of Current Pharmaceutical Research, 2020)
Objective: Environmental concerns have prompted research into the development of biodegradable polymer as an alternative to petroleum-based plastics. Polyhydroxybutyrates (PHBs) are good alternatives to produce biodegradable plastics. Some bacteria are found to be producing PHB. The aim of this work was to isolate potential PHB producing bacteria and screen them for their ability to produce PHB. Methods: Contaminated water sample from Gopalpur beach, Bhubaneswar was the source of bacteria. Three colonies were isolated from the water sample. The samples were named as C1, C2 and C3. The colonies were first identified by colony morphology. The sudan black screening test was done to screen for the production of (PHB) polyhydroxy butyrate by bacterial isolates. Results: The bacterial isolates C1 and C2 showed a positive result for the production of polyhydroxy butyrate (PHB). Presence of PHB granules in Cocobacillus and Rod shaped bacillus was confirmed. Conclusion: Polyhydroxybutyrate (PHB), a kind of microbial polyester that accumulates as a carbon/energy reserve material in various microorganisms, was thus concluded to be a decent alternative for plastics. Because of their special characteristics and broad biological applications, biodegradable plastics are compounds with a promising future.